A rare case of recurrent pilonidal sinus of scalp - Kansal, Abhishek; Jain, Rajiv; Jain, Suraj; Munjal, Kavita (International Surgery Journal, 2016)
Pilonidal sinus can sometimes be found at the rare site. History of previous surgery can give important diagnostic clue. In the present study, we reported a case of a middle aged lady who has undergone surgery of scalp nodule for misdiagnosed infected sebaceous cyst. On evaluation and exploration, this turned out to be a recurrent pilonidal sinus of scalp. Pilonidal sinus should be included under the differential diagnosis of any long standing sinus over a hairy area.